Synthesisand characterization of secondary amine-functionalized silica for CO2 capture - Abdul Rahim, A.R. (IOP Publishing Ltd, 2021)
As one of commonly used technique for carbon dioxide (CO2) removal, amine-absorption also required high amounts of energy for adsorbent regeneration and problems of equipment corrosion during chemical holding may happened. Alternatively, amine-impregnated solid adsorbent received wide attention for CO2 removal. However, there are limitations on the adsorbentsâ adsorption capacity and their hydrolytic stability. In this study, amine-functionalized silica (T-Si) adsorbent was synthesized via oil-in-water emulsion technique using centrimonium bromide (CTAB) as surfactant, ethanol as oil phase, and tetraethyl orthosilicate (TEOS) as silica precursor followed with impregnation with secondary amine (tetraethyl pentamine, TEPA). Results indicated that T-Si2 adsorbent has a surface area of 10.7338 m2/g, presence of amine group (N-H) peaks in the FTIR spectra, and is thermally stable up to temperature of 170 oC. CO2 adsorption study also shows that the T-Si also performed higher adsorption capacity (0.63 mmol/g) towards CO2 compared to the blank Si adsorbent (0.33 mmol/g). The obtained experimental data show a good fitting into Sips adsorption isotherm which indicate a multilayer adsorption that happen on a heterogenous surface. The findings of this study show that the introduction of amine groups from TEPA offers improvement towards CO2 capture due to the reaction with amine groups. Â© 2021 Institute of Physics Publishing. All rights reserved.